Pengaruh Kualitas Produk, Harga, Dan Promosi Terhadap Keputusan Pembelian Mie Instan Merek Indomie - Ratna Ariyanti; Rayhan Gunaningrat (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
In today's modern era, a person has many activities that must be carried out. With the existing conditions, consumers will automatically look for something that can support their daily lives more effectively and efficiently, which if we compare it with the present, one of these things will lead to instant foods. One food that is very popular and trusted among the wider community is instant noodle food products. This research aims to determine and analyze the influence of product quality, price, promotion on purchasing decisions for Indomie brand instant noodles among consumers in Solo. The data collection method was carried out by distributing questionnaires online using Google Form with a total of 56 respondents. The analysis technique used is multiple linear regression using SPSS version 26 software tools. The results obtained in this research show that product quality has no significant influence on purchasing decisions, price has a significant influence on purchasing decisions, and promotions have an influence on purchasing decisions.